Highly solar reflectance and infrared transparent porous coating for non-contact heat dissipations - Chen, Meijie; Pang, Dan; Yan, Hongjie (iScience, 2022)
Passive daytime radiative cooling (PDRC) can dissipate heat to outer space with high solar reflectance (R¯solar) and thermal emittance (ε¯LWIR) in the atmospheric transmission window. However, for the non-contact heat dissipation, besides the high R¯solar, a high infrared transmittance (τ¯LWIR) is needed to directly emit thermal radiation through the IR-transparent coating to outer space. In this work, An IR-transparent porous PE (P-PE) coating with R¯solar= 0.96 and τ¯LWIR= 0.88 was prepared for non-contact heat dissipations. Under the direct sunlight of 860 W m−2, the IR-transparent coating obtained a 4°C lower heater temperature than the normal PDRC coating under the same condition. In addition, the spectral reflectance of the P-PE coating after immersing in air or water changed little, which showed excellent durability for long-term outdoor applications. These results indicate the P-PE coating can be a potential IR-transparent coating for non-contact heat dissipations under direct sunlight. [Display omitted] •Infrared transparent coating was used for non-contact heat dissipations•High solar reflectance R¯solar and IR-transmittance τ¯LWIR can be 0.96 and 0.88•IR transparent coating obtained a 4°C lower heater temperature than normal coating Energy sustainability; Thermal engineering; Thermal property